Daya Antibakteri Infusa Kismis (Vitis vinifera L.) Konsentrasi 100%, 50%, dan 25% Terhadap Streptococcus mutans (Antibacterial Activity of Raisins Infuse (Vitis vinifera L.) Concentration 100%, 50%, and 25% Against Streptococcus mutans) - Dian Fajariani; Achmad Gunadi; Melok Aris Wahyukundari (Pustaka Kesehatan, 2017)
Background: Dental plaque is one factor that causing the occurrence of dentalcaries and periodontal disease. Bacteria that has role in the process offorming and increasing the accumulation of dental plaque is Streptococcusmutans. S. mutans digest sucrose and synthesis glukan in order to helpother bacterial adhesions to form plaques biofilm. An effective way to controlplaque accumulation is needed. One of the ways is using mouth rinse.The mouth rinse in the market could give some side effect in long term.Raisin is a food that made from dried grape result which consists of antimicrobialsubstance such as flavonoid, tannin and triterpenoid. Objective: Determinedthe large of antibacterial activity and effective concentration ofraisins infused that still have antibacterial activity against S. mutans. Methods:This study was laboratories experimental with post test only control groupdesign research. The method was using well diffusion method. Antibacterialactivity was showed by the inhibition zone around the well. Total of researchsamples were 25 samples which divided into 5 groups that were 25%, 50%,100% concentration of raisins infused, chlorhexidine 0,2% and sterileaquadest. Result and Conclusion: The magnitude of antibacterial activityraisins infused against S. mutans was achieved by consentration of 100%,50%, 25% respectively and the effective concentration of the raisins infusedwhich had antibacterial activity was 100%.